The Impression Management: Meaning, Manifestations, Ways of Identifying - Shchetinina Ludmila V.; Rudakova Svetlana G.; Fedortsova Maryna S. (Bìznes Inform, 2019)
The article is aimed at identifying the current trends in the field of impression management based on sociological research and developing recommendations to managers, employees of services for personnel management. In the course of a sociological survey is identified that 91% of respondents usually try to make a positive impression of themselves. The main reasons for impression managing are the desire: to have good relations with colleagues at work - 71%, to have useful connections - 44%, to get a benefit for one’s self - 33%; to look perfect in the eyes of others - 29% of respondents. It is important that 48% of respondents said that they did manage their impressions to achieve their own goals, and another 13% did not, but would like to know about the strategy of managing impressions. The negative consequences of managing impressions, according to respondents, are the loss of trust in the person, the emergence of a strong desire to stop communicating with the person, as well as the ability to make erroneous managerial decisions. The relevance of learning impression management techniques increases as their use is being spread. Therefore, the elaborated ways to identify them will be needed by specialists to neutralize the negative impact, make the right managerial decisions, form an objective impression of a person.